Facing decay : beauty, aging, and cosmetics in early modern Europe - Griffey, Erin (The Pennsylvania State University Press, 2025)
"Examines how early modern women sought to preserve youth and combat signs of aging through therapeutic cosmetics. Explores beauty practices as sites of medical knowledge, scientific innovation, and cultural agency, offering insight into historical attitudes toward aging, especially for women"-- Provided by publisher